The handbook of photonics - Gupta, M. C. (Mool Chand); Ballato, John (CRC Press, 2007)
Reflecting changes in the field in the ten years since the publication of the first edition, The Handbook of Photonics, Second Edition explores recent advances that have affected this technology. In this new, updated second edition editor Mool Gupta is joined by John Ballato, strengthening the handbook with their combined knowledge and the continued contributions of world-class researchers.